Surreal Femininity: Nature and “Woman” in the Art of Marguerite Humeau - Golovchenko, Margaryta (Journal of Posthumanism, 2021)
This paper focuses on the work of contemporary French artist Marguerite Humeau, specifically her 2018-19 exhibition “Birth Canal” and her 2016-17 exhibition “FOXP2.” Building on Surrealism’s interest in subverting the viewer’s notion of the real, the two exhibitions expand and reimagine the relationship between Woman, Nature, and the automaton. Humeau’s work makes the viewer question their understanding of gender, particularly whether behaviours that are codified as “female” in humans can easily be transposed onto the mechanical and the natural worlds. While the physical sculptures push the boundary between living and non, organic and mechanical, sound also plays an integral role in Humeau’s work by serving as the sculptures’ “voice.” In doing so, Humeau allows the nonhuman body to speak for itself, thereby undermining the Romantic notion of Nature as a sublime but passive muse.